LIQUISOLID COMPACTS: AN INNOVATIVE APPROACH FOR DISSOLUTION ENHANCEMENT - Anil, Anjana; Thomas, Litha; Sudheer, Preethi (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
The challenge faced by the majority of the pharmaceutical products is the poor solubility of the drug candidates which leads to low bioavailability. Liquisolid compact is one of the emerging techniques that enhances the dissolution of poorly water soluble drugs. Liquisolid system mentions to the formulation made by the transforming the liquid drug, either in the form of suspension or solution in non volatile solvents into a dry, non-sticky, free-flowing and compactable powder mixtures. This is achieved by mixing the suspension or solution of the drug with appropriate carriers and coating agents. The technology has the ability to increase aqueous solubility, rate of dissolution and absorption of poorly soluble drug by keeping it in molecularly dispersed form leading to its improved bioavailability when compared to conventional tablets. Liquisolid technology is the impending approach for enhancing the solubility of poorly water-soluble drug by adopting simple manufacturing process and low production cost.